2011
DOI: 10.1021/ac2001302
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Arrayed Imaging Reflectometry Biosensor Response for Protein–Antibody Interactions: Cross-Correlation of Theory, Experiment, and Complementary Techniques

Abstract: One of the critical steps in the development of an analytical technique is to confirm that its experimental response correlates with predictions derived from the theoretical framework on which it is based. This validates the technique quantitatively, and, in the case of a biosensor, facilitates a correlation of the sensor’s output signal to the concentration of the analyte being tested. Herein we report studies demonstrating that the quantitative response of Arrayed Imaging Reflectometry (AIR), a highly sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…6 The technique has also been validated via comparisons to reference methods including surface plasmon resonance (SPR) and spectroscopic ellipsometry. 7 With regard to influenza-targeted applications, we have demonstrated that multiplex hemagglutinin arrays have utility for rapidly assessing human serum samples for the presence of anti-influenza antibodies in a vaccine trial, 8 and provide a simple method for multiplex serology on avian surveillance samples. 9 Here, we provide a preliminary description of an AIR array intended to simplify the task of classifying newly observed strains of influenza, by enabling patterns of reactivity with the chip to be compared with those generated by known strains of the virus.…”
Section: Bound Probementioning
confidence: 99%
“…6 The technique has also been validated via comparisons to reference methods including surface plasmon resonance (SPR) and spectroscopic ellipsometry. 7 With regard to influenza-targeted applications, we have demonstrated that multiplex hemagglutinin arrays have utility for rapidly assessing human serum samples for the presence of anti-influenza antibodies in a vaccine trial, 8 and provide a simple method for multiplex serology on avian surveillance samples. 9 Here, we provide a preliminary description of an AIR array intended to simplify the task of classifying newly observed strains of influenza, by enabling patterns of reactivity with the chip to be compared with those generated by known strains of the virus.…”
Section: Bound Probementioning
confidence: 99%
“…AFM silicon nitride (Si 3 N 4 ) tips (Benyuan Nano Instrument Co., China) were covalently attached by the aptamer (or antibody) according to previously reported procedures. 20−22 In detail, the tips were first cleaned and hydroxized through the treatment with chloroform, HF acid, alkaline solution (NH 4 The cleaned tips were incubated in 1.0% (v/v) MPTMS/ toluene solution for 2 h and then rinsed thoroughly with toluene to be modified with −SH groups. Then, the silanized tips were activated by incubation with NHS-PEG-MAL (1 mg mL −1 ) in 50% dimethyl sulfoxide for 3 h at room temperature.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Many applications of biosensors in the literature heavily depend on the utilization of proteins as the recognition elements of the biosensor of interest [73]. They have also been utilized in many different FRET applications, and dye-conjugated proteins served as the acceptor or donor molecules.…”
Section: Monitoring Protein Involved Fret Processesmentioning
confidence: 99%